حول كتاب "الإمامة عند الإباضية" للشهيد بكير وعلي - قسوم, عبد الرزاق (الحياة, 2000)
Keywords: Recension

Review of Zanzibar: A Plan for the Historic Stone Town; Doors of Zanzibar - Frankl, P.J.L. (British Journal of Middle Eastern Studies, 2000)
Keywords: Recension

Review of The Emergence of States in a Tribal Society: Oman under Sa‛id bin Taymur, 1932-1970 - Ochsenwald, William (The American Historical Review, 2008)
Keywords: Recension

Review of In the Shadow of the Ancestors: The Prehistoric Foundations of the Early Arabian Civilization in Oman - Magee, Peter (American Journal of Archaeology, 2008)
Keywords: Recension

Review of In the Shadow of the Ancestors. The Prehistoric Foundations of the Early Arabian Civilization in Oman - Lombard, Pierre (Paléorient, 2009)
Keywords: Recension

Review of The Epistle of Sālim Ibn Dhawān - Gilliot, Claude (Studia Islamica, 2003)
Keywords: Recension

Review of Historical Mosques and Shrines of Oman (BAR International Series, 938) - Comneno, Maria Adelaide Lala (Quaderni di Studi Arabi, 2002)
Keywords: Recension

Review of Oman: Political Development in a Changing World - Deeb, Mary-Jane (The American Political Science Review, 2001)
Keywords: Recension

Review of Oman under Qaboos: From Coup to Constitution, 1970-1996, W. Lynn Rigsbee, II - Peterson, John E. (Middle East Journal, 2001)
Keywords: Recension

Oman Under Qaboos: From Coup to Constitution, 1970-1996; Calvin Allen, Jr.; W. Lynn Rigsbee II - Farah, Caesar E. (Digest of Middle East Studies, 2000)
Keywords: Recension

Marc Lavergne, Brigitte Dumortier : L’Oman contemporain. État, territoire, identité - Bondue, Jean-Pierre (Espace populations sociétés. Space populations societies, 2004)
Keywords: Recension

Lavergne M. et Dumortier B. (dir.), L'Oman contemporain. État, territoire, identité - Troin, Jean-François (Annales de géographie, 2003)
Keywords: Recension

Review of In the Wake of the Dhow: The Arabian Gulf and Oman - Ray, Himanshu Prabha (Journal of the Economic and Social History of the Orient, 2003)
Keywords: Recension

Jeffrey T. Kenney, Muslim Rebels: Kharijites and the Politics of Extremism in Egypt (Oxford: Oxford University Press, 2006). Pp. 234. $45.00 cloth. - Kalmbach, Hilary (International Journal of Middle East Studies, 2009)
Keywords: Recension

Review of Oman: The Islamic Democratic Tradition - Solomon, Gina; Latorre, Aida (Middle East Studies Association Bulletin, 2007)
Keywords: Recension

Latifah al-Bakkay, Harakat al-Khawarij. Nash'atuha wa-tatawwuruha ila nihayat al-'ahd al-umawi (37-132 H.) - Melchert, Christopher (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2002)
Keywords: Recension

Review of The Emergence of States in a Tribal Society: Oman under Sa'id bin Taymur, 1932-1970 - Allen, Jr, Calvin H. (Middle East Journal, 2007)
Keywords: Recension

Review of Oman: The Islamic Democratic Tradition - Allen, Jr, Calvin H. (International Journal of Middle East Studies, 2008)
Keywords: Recension

Review of In the Wake of the Dhow: The Arabian Gulf and Oman - Allen, Jr, Calvin H. (International Journal of Middle East Studies, 2004)
Keywords: Recension

Bernardie-Tahir, Nathalie (dir.) (2008) L’autre Zanzibar. Géographie d’une contre-insularité. Paris, Karthala, 379 p. (ISBN 978-2-84586-946-2) - Bouchard, Christian (Cahiers de géographie du Québec, 2009)
Un article de la revue Cahiers de géographie du Québec, diffusée par la plateforme Érudit.
Keywords: Recension

Review of Il sultanato di Zanzibar nel XIX secolo: traffici commerciali e relazioni internazionali; Makran, Oman and Zanzibar. Three-Terminal Cultural Corridor in the Western Indian Ocean (1799-1856), Beatrice Nicolini - Bernardi, Bernardo (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 2006)
Keywords: Recension

Review of Changing Rural Systems in Oman. The Khabura Project - Pater, Ben de (GeoJournal, 2000)
Keywords: Recension

Review of Makran, Oman and Zanzibar. Three-Terminal Cultural Corridor in the Western Indian Ocean (1799-1856) - Loimeier, Roman (Die Welt des Islams, 2006)
Keywords: Recension

Review of Mehri Texts from Oman (Based on Field Materials of T. M. Johnstone) - Kaye, Alan S. (Journal of the American Oriental Society, 2001)
Keywords: Recension

Review of In the Wake of the Dhow - Kaye, Alan S. (Bulletin of the School of Oriental and African Studies, 2003)
Keywords: Recension

Dhows and the Colonial Economy of Zanzibar, 1860-1970 - Sheriff, Abdul Mohamed Hussein (Economic History Association, 2005)
Keywords: Recension

Review : Makran, Oman and Zanzibar: Three-Terminal Culural Corridor in the Western Indian Ocean, 1799-1856, Beatrice Nicolini, Leiden: E. J. Brill, 2004. ISBN 9004137807, xxvii + 179 pp., index, four illustrations - Limbert, Mandana E. (Iranian Studies, 2006)
Keywords: Recension

أثر تحقيق رسالة بن ذكوان في تطور الدراسات حول الأباضية - قطاط, فريد (الحياة الثقافية, 2004)
Keywords: Recension

Review : Makran, Oman, and Zanzibar: Three-Terminal Cultural Corridor in the Western Indian Ocean (1799-1856), trans. Penelope-Jane Watson, Islam in Africa Series, vol. 3 (Leiden: Brill, 2004). Pp. 191. $112.00 cloth. - Risso, Patricia (International Journal of Middle East Studies, 2005)
Keywords: Recension

Une enfance dans M'Zâb de Abderrahmane Zakad. Éditions Alpha, Alger, 2008, 226 pages. (L'Expressiondz, 2008)
Keywords: Recension

Review : Muhammad al-Mahruqi (ed.), Mugamir 'umani fi adgal Ifriqya. Hayat Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1905), al-ma'riif bi-TibuTib [Un aventurier Omanais au coeur de l'Afrique. La vie de Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1900), connu sous le nom de Tippo Tip], Cologne, Al-Kamel, 2006 (210 p.). - Luffin, Xavier (Annales Aequatoria, 2008)
Keywords: Recension; Tippo Tip (1837-1905)

Review : Oman under Qaboos. From Coup to Constitution, 1970-1996 - Hertog, Stephen (British Journal of Middle Eastern Studies, 2007)
Keywords: Recension

Review: [Muslim Rebels: Kharijites and the Politics of Extremism in Egypt, by Jeffrey T. Kenney. New York: Oxford University Press, 2006. xi + 184 pages. Notes to p. 205. Bibl. to p. 216. Indexto p. 221. $45.] - Jankowski, James (Middle East Journal, 2007)
Keywords: Recension

Review: Mehri Texts from Oman: Based on the Field Materials of T. M. Johnstone, by Harry Stroomer. (Semitica Viva, Bd. 22) 303 pages, map, bibliography, footnotes, transcription table. Wiesbaden, Germany: Harrassowitz Verlag, 1999. DM168.00 (Paper) isbn 3-447-04215-X - Cross, Carmen (Middle East Studies Association Bulletin, 2001)
Keywords: Recension

Review : Hoffmann-Ruf, Michaela: Scheich Muhsin bin Zahrän al-'Abri. Tribale Macht im Oman des 19. Jahrhunderts. Berlin (Klaus Schwarz) 2008. 46 Euro. ISBN 978-3-97997-353-8. - Lohlker, Rüdiger (Wiener Zeitschrift für die Kunde des Morgenlandes, 2009)
Keywords: Recension

Review: Seafaring in the Arabian Gulf and Oman: The People of the Dhow, by DIONISIUS A. AGIUS. London: Kegan Paul, 2005.285 pages, illustrations,glossary,name index. UK<£95.00 (Cloth) ISBN 0-7103-0939-2 - Nicolini, Beatrice (Middle East Studies Association Bulletin, 2006)
Keywords: Recension

Mulāḥaẓāt ḥawla Kitāb “al-Lawwāḥ al-Kharūṣī” - Būḥajjām, Muḥammad b. Qāsim Nāṣir (2004)
FMC A review of Ḥusaynī, Rāshid b. Ḥamad 1996.
Keywords: Recension

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Ibrahim (International Journal of Middle East Studies, 2000)
Keywords: Recension

Review : Cook, Michael: (2000) Commanding right and forbidding wrong in Islamic thought. Cambridge: Cambridge University Press, 2000, (xvii, 702 pp.; 23x15 cm.). ISBN 0521661749. - Sajjad, Rizvi (Transcendent Philosophy, 2001)
Keywords: Recension

Review : Traditional Arts in Southern Arabia: Music and Society in Sohar, Sultanate of Oman - Urkevich, Lisa (The World of Music, 2009)
Keywords: Recension

Review : Bendrissou Salah, Implantation des Mozabites dans l’Algérois entre les deux-guerres - Ben Madani, Mohamed (The Maghreb Review, 2003)
Keywords: Recension

Ersilia Francesca. Teoria e pratica del commercio nell’Islam medievale. I contratti di vendita e di commenda nel diritto ibadita - Aguirre Sádaba, F. J. (Jerusalem Studies in Arabic and Islam, 2004)
Keywords: Recension

The Emergence of States in a Tribal Society: Oman under Sa'id bin Taymur, 1932-1970by Uzi Rabi - Kechichian, Joseph Albert (The International History Review, 2007)
Keywords: Recension

Uzi Rabi. The Emergence of States in a Tribal Society: Oman under Sa‘id bin Taymur, 1932–1970 .:The Emergence of States in a Tribal Society: Oman under Sa ^ʕ id bin Taymur, 1932–1970 - Ochsenwald, William (The American Historical Review, 2008)
Keywords: Recension

Uzi Rabi The Emergence of States in a Tribal Society: Oman under Saʿid bin Taymur, 1932–1970 (Portland, Ore.: Sussex Academic Press, 2006). Pp. 320. $67.50 cloth. - Riphenburg, Carol J. (International Journal of Middle East Studies, 2008)
Keywords: Recension

Oman under Qabus: From Coup to Constitution, 1970-1996 by Calvin Allen, Jr.; W. Lynn Rigsbee, II - Rabi, Uzi (Middle Eastern Studies, 2001)
Keywords: Recension; Vie politique – Oman – 1970-2020

The Emergence of States in a Tribal Society: Oman Under Sa'id bin Taymur, 1932-1970 : Uzi Rabi - Silverberg, Sanford R. (Digest of Middle East Studies, 2008)
Keywords: Recension

The Epistle of Sālim ibn Dhakwān, by Patricia Crone and Fritz Zimmermann. New York: Oxford University Press, 2001. 407 pages, appendices, bibliography. US $90.00 (cloth) ISBN 0-19-815265-5 - Jarrar, Maher (Middle East Studies Association Bulletin, 2003)
Keywords: Recension

P. Crone and F. W. Zimmermann: The Epistle of Salim Ibn Dhakwan. (oxford Oriental Monographs.) Xi, 407 Pp. Oxford: Oxford University Press, 2001. £65. - Melchert, Christopher (Bulletin of the School of Oriental and African Studies, 2002)
Keywords: Recension

أبناء جزيرة جربة في الحركة الوطنية 1881-1961 - الصغير, عميرة علية (مجلة روافد, 2008)
Keywords: Recension

Rabah NABLI, Les Entrepreneurs tunisiens. La difficile émergence d’un nouvel acteur - Ferréol, Gilles (Revue européenne des migrations internationales, 2009)
Keywords: Recension

Oman: A Thousand Years of Democratic Tradition * by Hussain Ghubash - Jones, Jeremy (Journal of Islamic Studies, 2007)
Keywords: Recension

PREVOST, V .- L'aventure ibadite dans le Sud tunisien (VIIle-xrne siècle). Effervescence d'une région méconnue. - Custers, Martin H. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Ibadi publishing activities in the East and in the West c. 1880-1960s. An attempt to an inventory, with references to related recent publications - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Al-Ibadiyya. A bibliography. Volume 1: Ibadis of the Mashriq; Volume 2: Ibadïs of the Maghrib (incl. Egypt); Volume 3: Secondary literature - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

Cohen-Tannoudji Denis (dir.), Entre orient et occident, Juifs et Musulmans en Tunisie, Paris, Éditions de l’éclat, 2007, 379 p. - Abécassis, Frédéric (Revue des mondes musulmans et de la Méditerranée, 2009)
Ce livre est le produit d’une rencontre, tenue à la Sorbonne en avril 2003, entre chercheurs français, tunisiens et israéliens à l’initiative de la Société d’histoire des Juifs de Tunisie. Le colloque s’est tenu sous le quadruple patronage de l’UNESCO, du CNRS, des ministères des Affaires étrangères et de l’Éducation nationale, en impliquant bien d’autres acteurs institutionnels. Sans qu’il n’y soit jamais fait référence, l’ouvrage, paru quatre ans plus tard, porte la marque du contexte dans ...
Keywords: Recension

A Modern History of Oman: Formation of the State Since 1920By Francis Owtram (London: I. B. Tauris, 2004). 232 pp. Price HB £35.00. ISBN 1-86064-617-4 - Jones, Jeremy (Journal of Islamic Studies, 2006)
Keywords: Recension

Patricia CRONE and Fritz ZIMMERMANN: The, Epistle of Salim ibn Dhakwan. Oxford, 2001: Oxford University Press, xii, 407 pp. ISBN O 19 815265 5. £ 65.00. - Conrad, Lawrence (Der Islam, 2004)
Keywords: Recension

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Bonner, Michael (Journal of the American Oriental Society, 2000)
Keywords: Recension

PREVOST, Virginie, L'aventure ibadite dans le Sud tunisien (VIIIe-XIIIe siècle). Effervescence d'une région méconnue, Tuusula y Helsinki: Academia Scientiarum Fennica, "Humaniora 350", 2008, 479 págs., ilustraciones. - Viguerra Molins, Maria Jesus (Anaquel de Estudios Árabes, 2009)
Keywords: Recension

The homecoming - Halberstadt, Ilona (Sight and Sound, 2001)
Keywords: Recension

Tunisie: La mémoire des Juifs de Djerba. Yaacov Bchiri - Weissenberg, Luc (Cahiers de musiques traditionnelles, 2001)
Keywords: Judaïsme – Djerba; Recension

Review of Dhows and the Colonial Economy of Zanzibar, 1860-1970 - Hoag, Heather J. (The International Journal of African Historical Studies, 2005)
Keywords: Recension